Pengembangan Fitur Chat Pada Website PT. Danatrans Service Logistics - R. Mochammad Armand Giri Seno; arief jananto (Elkom : Jurnal Elektronika dan Komputer, 2024)
PT. Danatrans Service Logistics has website-based information media, but the website only displays the services offered and if a customer wants to ask, they have to retype the PT email address. Danatrans Service Logistics will of course take quite a long time, so it will reduce the quality of service provided to customers via the website. This research has succeeded in developing the PT website. Danatrans Service Logistics with chat facilities between customers and the Billing, Customer Service, Document Requirements, Delivery, Emergency Services, Security & Insurance and Shipping Costs sections at PT. Danatrans Service Logistics so that it can improve the quality of customer service. Another feature in this research is chat statistics and chat grouping between admin and PT customers. Danatrans Service Logistics